Revitalización sindical y sindicalismo peronista : encrucijadas entre el corporativismo y la política (Argentina, 2003-2012) - Ana Natalucci (Les Cahiers ALHIM)
The literature agrees that after 2002 occurred a process of revival of trade union linked to the recovery of certain rights accompanied by a growing demand for political participation. How to explain the process that repositioned articulators unions as workers' demands and demands for political intervention ? What is the analytical productivity of the notion of union revitalization ? The purpose of this paper is to investigate the process from transformations in the labor movement that allowed the emergence of labor-based political organizations like the Juventud Sindical, collective adherent to Corriente Nacional del Sindicalismo Peronista, headed by Hugo Moyano. The argument is that the revival was a process oriented bounded restitution corporate bargaining power. However, as shown in the case of the Juventud Sindical, the organizations were not only workers' demands, but hoped to regain their status as political subjects. At this juncture it is possible to understand the dynamics of trade unionism in the history recent.